Business and financial management - Watts, B K R. (Plymouth : Macdonald and Evans, Longman, 1988)
Explains in lucid style the mechanisms of the unlisted securities markets, referrals to the OFT, small business finance and many other topical issues; includes up-to-date financial statistics and information on the high level of acquisition and merger activity.
First ed. published under title: Industry and finance.
Includes index.
oif 04/11/14
Loan
Keywords: Finance; Industries; Corporations; Financial management